n2-1=n6+1

Subtract n6 from both sides of the equation.

n2-1-n6=1

To write n2 as a fraction with a common denominator, multiply by 33.

n2⋅33-n6-1=1

Write each expression with a common denominator of 6, by multiplying each by an appropriate factor of 1.

Multiply n2 and 33.

n⋅32⋅3-n6-1=1

Multiply 2 by 3.

n⋅36-n6-1=1

n⋅36-n6-1=1

Combine the numerators over the common denominator.

n⋅3-n6-1=1

Subtract n from n⋅3.

Reorder n and 3.

3⋅n-n6-1=1

Subtract n from 3⋅n.

2⋅n6-1=1

2⋅n6-1=1

Cancel the common factor of 2 and 6.

Factor 2 out of 2⋅n.

2(n)6-1=1

Cancel the common factors.

Factor 2 out of 6.

2n2⋅3-1=1

Cancel the common factor.

2n2⋅3-1=1

Rewrite the expression.

n3-1=1

n3-1=1

n3-1=1

n3-1=1

Add 1 to both sides of the equation.

n3=1+1

Add 1 and 1.

n3=2

n3=2

Multiply both sides of the equation by 3.

3⋅n3=3⋅2

Cancel the common factor of 3.

Cancel the common factor.

3⋅n3=3⋅2

Rewrite the expression.

n=3⋅2

n=3⋅2

Multiply 3 by 2.

n=6

n=6

Solve for n n/2-1=n/6+1